2009
DOI: 10.1096/fj.09-134346
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of SNARE‐dependent exocytosis to inflammatory potentiation of TRPV1 in nociceptors

Abstract: Potentiation of the pain-integrator ion channel transient receptor potential vanilloid type 1 (TRPV1) underlies thermal hyperalgesia mediated by a variety of proinflammatory factors. Two complementary mechanisms of TRPV1 inflammatory sensitization have been proposed, namely a decrease of its activation threshold and an increment of its surface expression in nociceptors. Here we investigated the involvement of regulated exocytosis to the inflammatory sensitization of TRPV1 in rat neonatal dorsal root ganglion n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(162 citation statements)
references
References 45 publications
8
152
2
Order By: Relevance
“…However, the contribution of TRPV1 mobilization from the plasma membrane to intracellular reservoirs as a mechanism to attenuate nociceptor overactivity has not yet been evaluated in detail. We and others have shown that TRPV1 sensitization is achieved at least in part by rapid recruitment of a subcellular population of vesicular TRPV1 that becomes translocated to the plasma membrane by regulated exocytosis under inflammatory conditions (21,23,36). Therefore, the opposite mechanism, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the contribution of TRPV1 mobilization from the plasma membrane to intracellular reservoirs as a mechanism to attenuate nociceptor overactivity has not yet been evaluated in detail. We and others have shown that TRPV1 sensitization is achieved at least in part by rapid recruitment of a subcellular population of vesicular TRPV1 that becomes translocated to the plasma membrane by regulated exocytosis under inflammatory conditions (21,23,36). Therefore, the opposite mechanism, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…23. HEK293 cells were cultured as described (24) and used 48 h after transfection with TurboFect (Fermentas Life Sciences) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Bradykinin was shown to cause translocation of PKC in cultured DRG neurons (746). Considerable evidence has been provided for the involvement of PKC in the various excitatory (nocifensive or spikegenerating) and sensitizing effects of bradykinin studying transfected cells, cultured sensory neurons (85,94,95,120,296,411,435,585,586,685,745,764; see details in sect. IIC3), nerve fiber discharge (252,253,497), nocifensive behavior (186), and neuropeptide release (200).…”
Section: Plc Pkc and Intracellular Ca 2ϩ In Bradykinin Receptor Sigmentioning
confidence: 99%
“…As a transmembrane receptor, the number of functional TRPV1s at the plasma membrane must be a critical determinant of channel function, and potentiating channel function by increasing its levels at the cell surface is a potential mechanism underlying proinflammatory mediator-induced heat hyperalgesia (Ji et al, 2002;Van Buren et al, 2005;Zhang et al, 2005;Stein et al, 2006;Camprubí-Robles et al, 2009). In general, the number of receptors at the surface can be regulated by the membrane trafficking and insertion of receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the number of receptors at the surface can be regulated by the membrane trafficking and insertion of receptors. To date, studies have shown that PKC activation-sensitized SNARE-dependent exocytosis and Src-dependent phosphorylation of TRPV1 are involved in inflammatory stimuli-induced rapid membrane insertion of TRPV1s from a ready-to-go vesicular pool (Morenilla-Palao et al, 2004;Zhang et al, 2005;Camprubí-Robles et al, 2009), but the mechanisms that regulate transport of TRPV1s from the Golgi apparatus to the plasma membrane of sensory neurons is essentially unclear. Kinesin superfamily motor proteins are responsible for the intracellular anterograde transport of most cargos, including transmembrane receptors (Hirokawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%